The burden of malnutrition & frailty in patients with coronary artery disease: An under-recognized problem. (May 2022) - Arshad, Samiullah; Khan, Samina; Karim, Adham; Gupta, Vedant A.
Elderly patients with coronary artery disease have a high prevalence of frailty and malnutrition. Frailty syndrome is associated with poor outcomes in patients with myocardial infarction. There is a known overlap between frailty and malnutrition, yet these are two different entities. Fried Frailty Phenotype, Frail Scale, timed up and go test, and gait speed are rapid screening tests that may identify patients with frailty in everyday clinical setting. Short Form MNA is a sensitive tool to screen for malnutrition. Despite the availability of several tools for screening for both these conditions, the screening rates remain low. We aim to create awareness about the impacts of frailty and malnutrition, provide a brief overview of tools available and highlight the importance of screening in this high-risk population.